2007
DOI: 10.1016/j.ejphar.2007.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and chronic apomorphine on sex behavior and copulation-induced neural activation in the male rat

Abstract: Apomorphine is a non-selective dopaminergic receptor agonist. Because of its pro-erectile effects, apomorphine is clinically used for treatment of erectile dysfunction. We investigated the effects of subcutaneous apomorphine administration (0.4 mg/kg rat) on sexual behavior and matinginduced Fos-expression following acute (day 1) or chronic apomorphine treatment (days 8 and 15) in sexually experienced male rats. Consistent facilitatory effects of apomorphine were observed in the reduced numbers of mounts and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 118 publications
(189 reference statements)
0
7
0
Order By: Relevance
“…This small and short-living facilitatory effect of bupropion was rather unexpected. Apomorphine [41], a mixed dopamine D 2 /D 3 receptor agonist showed a comparable profile in a similar experiment ( ↓: inhibition; ↑: stimulation; 0: no effect; nt: not tested. SSRI: selective serotonergic reuptake inhibitor; SNRI: serotonergic and noradrenergic reuptake inhibitor; NDRI: noradrenergic and dopaminergic reuptake inhibitor; TRI: triple monoaminergic reuptake inhibitor; R: receptor.…”
Section: Sexual Dysfunctionmentioning
confidence: 69%
“…This small and short-living facilitatory effect of bupropion was rather unexpected. Apomorphine [41], a mixed dopamine D 2 /D 3 receptor agonist showed a comparable profile in a similar experiment ( ↓: inhibition; ↑: stimulation; 0: no effect; nt: not tested. SSRI: selective serotonergic reuptake inhibitor; SNRI: serotonergic and noradrenergic reuptake inhibitor; NDRI: noradrenergic and dopaminergic reuptake inhibitor; TRI: triple monoaminergic reuptake inhibitor; R: receptor.…”
Section: Sexual Dysfunctionmentioning
confidence: 69%
“…It has been demonstrated that fictive ejaculation can be pharmacologically induced by the systemic injection of dopamine or apomorphine acting at the spinal generator for ejaculation [21,33,34,44] and it has been considered as the main model for the study of the spinal pattern generator of ejaculation [8]. Thus, with no doubt, the effect of the aphrodisiac plants could be systemically evaluated by using the fictive ejaculation model and particular results, highlight the differential effects of aphrodisiac plants.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence shows that dopamine is a neurotransmitter playing a central role in the control of ejaculation [31,32]. Thus, for instance, stimulation of dopaminergic receptors by systemic dopamine [21] or apomorphine [33,34] provokes the expression of ejaculation in spinal male rats. On the other side, systemic administration of antagonists of dopaminergic receptors abolishes the expression of the ejaculatory response in spinal rats [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…We have provided an overview of mechanisms through which different components of a female’s reproductive experiences can alter dopamine neurotransmission in a way that the system shows a sensitized response to drugs even upon the initial exposure. Our focus has been on reproductive events in females, though it is important to note that there is a rich literature in rats demonstrating that male sexual experience sensitizes the mesolimbic dopamine system [8,9,68,159,168,205] in much the same way as we have described for females.…”
Section: Discussionmentioning
confidence: 99%